Influence of Rock Bolt Support Parameters on Geomechanical Stability and Methane Emission in Longwall Mine Workings - R. Kamarov; Zh. Assanova; Sh. Zeitinova; Zh. Azimbayeva; J. Bogzhanova (Salehan Institute of Higher Education, 2026)
Under the conditions of the transition of the mines of the Karaganda Coal Basin to a high-productivity “mine–longwall” operating model, there is an increasing need to implement rational technologies for the development of mine workings that ensure higher drivage rates, reduced gas emission, and improved geomechanical stability of the rock mass. The purpose of this work is to study the influence of anchor support on the geomechanical and gas-dynamic state of the rock mass adjacent to the longwall mining area through a combination of field investigations and numerical flow modeling (ANSYS CFX), and to analyze the resulting properties of the side rocks and the stability of anchored mine workings. The research methodology included in situ observations under underground mining conditions, instrumental monitoring of roof displacement and rock stratification using KDM-1 and KDM-2 deformation control devices, analysis of outburst hazard indicators of the coal seam, and numerical simulation of methane distribution in mine workings using the Ansys CFX software package. The studies were carried out in development workings of the Kuzembayev Mine and the Saranskaya Mine at depths of 438–577 m. The results show that reducing the spacing between rock bolt rows to 0.5 m and increasing the bolt length to 2.4 m provides a reduction in vertical roof displacements to 5–30 mm and decreases absolute methane emission by 23%. The use of yielding rock bolt–frame support contributes to a reduction in the stress state of the rock mass, limits roof stratification, and eliminates manifestations of outburst hazard. The scientific novelty of the study lies in a comprehensive assessment of the relationship between rock bolt support parameters, the geomechanical condition of the rock mass, and gas emission, as well as in substantiating the effectiveness of yielding rock bolting systems in zones influenced by longwall mining under complex geological and mining conditions.